A Cautious New Approach - Zhang, Denghua (ANU Press, 2020)
"'As a student of international relations and a former diplomat, Zhang brings the insights of a practitioner and the eye of scholar to explain why Chinese actors choose to engage in aid cooperation with traditional donors in the Asia-Pacific. This book is among the first to take a holistic approach to understanding the motivations of the many agencies involved in China's aid program, and it will challenge the expectations of many readers.' -Dr Graeme Smith, The Australian National University 'This book breaks new ground by examining a little-known dimension of China's foreign policy: trilateral aid cooperation. Denghua Zhang sets this highly original analysis in the context of the new assertiveness of Chinese foreign policy under Xi Jinping, the China International Development Cooperation Agency established in 2018, and the Belt and Road Initiative, which now serves as the framework for Chinese overseas aid and engagement. At a time when the debate in the West about the rise of China has intensified, not always knowledgeably, this book fills an important gap in our understanding of China in Southeast Asia and the Pacific.' -Dr Stewart Firth, The Australian National University 'This thoroughly researched work examines trilateral cooperation as a new and interesting aspect of China's growing international aid program, and as a window into the changing nature of that program as well as the wider foreign policy in which it is embedded. The broad themes and topics discussed are clearly significant, ultimately touching on one of the most important international issues of our time, the implications of the rise of China for a long-established Western-dominated international system.' -Prof. Terence Smith-Wesley, University of Hawai'i"